Establishing Normative Values for Inter-Limb Kinetic Symmetry During Landing in Uninjured Adolescent Athletes - Adam W. VanZile; David M. Reineke; Matthew J. Snyder; Daniel D. Jones; Renee L. Dade; Thomas G. Almonroeder (International Journal of Sports Physical Therapy)
# Background